The Effectiveness of UMMI Method with IT Media in Al-Qur'an Learning at QTC AL-Mady - Chusnul Chotimah; Raharjo Raharjo; Abdul Rohman; Siti Nur'aini (At-Taqaddum, 2023)
This study aims to test the effectiveness of using the UMMI method with IT media in learning the Qur'an. The UMMI method is a method of learning the Qur'an that integrates reading, writing and memorizing skills in a structured and directed method. IT media is used to support the learning process by utilizing technology such as applications, video and audio. This research was conducted using a comparative quantitative research method with a sample of 60 students consisting of 30 students who were taught by the UMMI method with IT media and 30 students who were taught by conventional methods. The results showed that the use of the UMMI method with IT media was effective in increasing student achievement and students' perceptions of learning the Qur'an. Students taught by the UMMI method with IT media have higher learning achievements and provide positive responses to this method. Therefore, the use of the UMMI method with IT media can be a solution to improve Al-Qur'an learning that is more effective and interesting for students.